Catalysis-based specific detection and inhibition of tyrosinase and their application - Yunwei Qu; Qing Zhan; Shubo Du; Yang Ding; Bin Fang; Wei Du; Qiong Wu; Haidong Yu; Lin Li; Wei Huang (Elsevier, 2020)
Tyrosinase is an important enzyme in controlling the formation of melanin in melanosome, and plays a key role in the pigmentation of hair and skin. The abnormal expression or activation of tyrosinase is associated with several diseases such as albinism, vitiligo, melanoma and Parkinson disease. Excessive deposition of melanin could cause diseases such as freckles and brown spots in the human body, and it is also closely related to browning of fruits and vegetables and insect molting. Detecting and inhibiting the activity of tyrosinase is of extraordinary value in the progress of diagnosis and treatment of these diseases. Therefore, many selective optical detection probes and small molecular inhibitors have been developed, and have made significant contributions to the basic and clinical research on these diseases. In this paper, the detection and inhibition of tyrosinase and their application in whitening products are reviewed, with special emphasis on development of fluorescent probes and inhibitors. Hopefully, this review will help design more efficient and sensitive tyrosinase probes and inhibitors, as well as shed light on novel treatment of diseases such as melanoma.